Evaluating the beginner level of the pusat bahasa programs by using the kirkpatrick model - Dewi, Kadek Maya Cyntia; Padmadewi, Ni Nyoman; Utami, I.G.A Lokita Purnamika (Indonesian Research Journal in Education |IRJE|, 2025)
This research evaluated the effectiveness of the Pusat Bahasa program at Institut Teknologi dan Kesehatan Bali, especially on beginner-level students, using the Kirkpatrick Model as a framework. The data were collected from 35 beginner-level students through questionnaires, observation sheets, and interviews. The finding showed that 85% of the participants expressed satisfaction with the Pusat Bahasa program. The results indicated that the program efficiently increases students’ participation and interaction in classroom activities. However, some students expressed moderate satisfaction with the Pusat Bahasa program and highlighted the necessity of continuous program assessment and modification. Students also indicated that they wanted to speak with a native speaker. The high level of students’ satisfaction and active involvement indicates that the Pusat Bahasa program at Institut Teknologi dan Kesehatan Bali, especially for the beginner level, benefited students’ learning experiences. The increased level of classroom interaction suggests that the program design is appropriate to suit the students’ needs. However, there was a clear need for program improvement.